2020
DOI: 10.1002/advs.202002320
|View full text |Cite
|
Sign up to set email alerts
|

2D Re‐Based Transition Metal Chalcogenides: Progress, Challenges, and Opportunities

Abstract: The rise of 2D transition-metal dichalcogenides (TMDs) materials has enormous implications for the scientific community and beyond. Among TMDs, ReX 2 (X = S, Se) has attracted significant interest regarding its unusual 1T′ structure and extraordinary properties in various fields during the past 7 years. For instance, ReX 2 possesses large bandgaps (ReSe 2 : 1.3 eV, ReS 2 : 1.6 eV), distinctive interlayer decoupling, and strong anisotropic properties, which endow more degree of freedom for constructing novel op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
70
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 215 publications
(368 reference statements)
2
70
0
Order By: Relevance
“…Atomically thin 2D transition metal dichalcogenides (TMDs) have drawn tremendous attention owing to their remarkable optical and electrical properties such as tunable bandgap and high carrier mobility for next-generation device applications. [1][2][3][4][5][6][7] Beyond the widely studied semiconducting TMDs (e.g., MoS 2 and WS 2 ), metallic TMDs (e.g., 1T 0 MoTe 2 /WTe 2 , PtTe 2 , and PdTe 2 ) with exotic properties offer a new platform for investigating newfangled F I G U R E 1 (A) Top view of PtTe 2 with 1T phase structure, and schematic band structure of type-I and type-II Dirac cones. (B) Schematic diagram of the controlled synthesis of atomic layer PtTe 2 via CVD method on solid and molten Au substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Atomically thin 2D transition metal dichalcogenides (TMDs) have drawn tremendous attention owing to their remarkable optical and electrical properties such as tunable bandgap and high carrier mobility for next-generation device applications. [1][2][3][4][5][6][7] Beyond the widely studied semiconducting TMDs (e.g., MoS 2 and WS 2 ), metallic TMDs (e.g., 1T 0 MoTe 2 /WTe 2 , PtTe 2 , and PdTe 2 ) with exotic properties offer a new platform for investigating newfangled F I G U R E 1 (A) Top view of PtTe 2 with 1T phase structure, and schematic band structure of type-I and type-II Dirac cones. (B) Schematic diagram of the controlled synthesis of atomic layer PtTe 2 via CVD method on solid and molten Au substrates.…”
Section: Introductionmentioning
confidence: 99%
“…First part highlights the top-down synthesis approach which comprises of mechanical and liquid phase exfoliations. Subsequent part discusses bottom-up techniques which includes the physical vapor deposition (PVD), chemical vapor transport (CVT) and chemical vapor deposition (CVD) techniques [ 52 ]. Depending on the applications’ need, various characterizations can be performed for the 2D TMD ReS 2 films.…”
Section: Structure Of Res 2 and Its Synthesis Methodsmentioning
confidence: 99%
“…A clean and flat substrate, usually SiO 2 /Si (300 nm) is then used to affix the freshly sliced thin flake from the scotch tape. Similarly, mono or few layers can be obtained and transferred to the targeted substrate [ 52 ]. A highly responsive phototransistors using few layers of ReS 2 is demonstrated by Liu et al [ 87 ] using mechanical exfoliation approach.…”
Section: Structure Of Res 2 and Its Synthesis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Take ReS 2 as an example, its monoclinic distorted octahedral (1T′) structure renders it optically and electrically biaxial, and thus endows it strong 2D in‐plane anisotropic properties and the accompanied brand new applications. [ 16–24 ] However, several recent studies have revealed that Re4‐chain reconstruction occurs easily with diverse manners during ReS 2 growth process, which brings plenty of sub‐domains and GBs in each ReS 2 domain, [ 25–29 ] as schematically shown in the top row of Figure . Accordingly, these sub‐domains with different lattice orientations lead to the optical and electrical properties varying dramatically in each ReS 2 domain, and the GBs seriously degrade its electrical transport properties.…”
Section: Introductionmentioning
confidence: 99%